THE GOOD PRACTICES CLAUSE IN THE “ACT ON COMBATTING UNFAIR COMPETITION OF 16 APRIL 1993” AND IN THE LIGHT OF SELECTED JURISPRUDENCE. THE ETHICAL IMPLICATIONS - Bider, Marcin (Management and Administration Journal, 2022)
This paper, employing historical-legal methods, presents selected court judgments on the good practices clause in the Act on Combatting Unfair Competition of 16 April 1993 (Ustawa o zwalczaniu nieuczciwej konkurencji z 16 kwietnia 1993 r.) (Journal of Laws 1993, No 47, item 211). The term unfair competition is used in the different legal categories in the act, which makes interpretation difficult. Each time the court determines the existence of two qualifications: entrepreneurs being in a court dispute conducting economic activity where there may be an infringement or a threat to the economic interests of the other entrepreneur. The innovative approach in this paper is based on what are ethical implications.